A REVIEW OF SERVANT AND TRANSFORMATIONAL LEADERSHIP STYLE IN ISLAMIC PERSPECTIVES: A LESSON FROM THE PROPHET MUHAMMAD (PBUH) AS AN EXCELLENT ROLE MODEL FOR MUSLIM LEADERS IN INDONESIA - Sulaeman Sulaeman (Nazharat: Jurnal Kebudayaan, 2020)
The purpose of this paper is to give a review of the servant and transformational leadership styles in Islam perspectives that have appeared in the literature. In so doing, the article provides the concept of the Islamic leadership model as a known dual-style Islamic leadership model by proposing the author. This paper used the narrative literature review methodology from previously publication such as textbooks and journal articles especially from primarly data - Qur’an and Sunnah. The study finds that two types of Islamic leadership were identified based on the leadership style of the prophet Muhammad (PBUH): servant and transformational leadership style. Furthermore, the paper provided a dual-style Islamic leadership model as effective leadership in practice for Muslim leaders in Indonesia. It is hoped that leaders such as managers, principals, CEOs in organizations/ corporations/social groups/communities would not hesitate to apply the Islamic leadership style especially dual-style Islamic leadership model. This paper will add to the literature on Islamic leadership style, especially for Muslim leaders in Indonesia